Development and performance analysis of a PIPS-based detection system for ultra-low Strontium-90 measurement in seawater - Kim, Younghak; Kim, Hyuncheol; Jang, Mee; Seo, Jaehyeon; Kim, Gahyun; Cha, Hyemi (Nuclear engineering and technology, 2025)
Strontium-90 (Sr-90) is a key radionuclide for monitoring because of its origin, physicochemical properties, and potential harm to human health. This radionuclide moves with seawater because of its high solubility and is found at trace levels, typically below 1 mBq/kg. Therefore, chemical pretreatment and a highly sensitive detection system are necessary to analyze the concentration of Sr-90 in seawater. In this study, we propose a prototype system based on a passivated implanted planar silicon (PIPS) detector to achieve a minimum detectable activity (MDA) comparable to conventional devices while enhancing user convenience. Finally, both passive and active shielding methods were applied to minimize background radiation contributions. The experimental results showed that the background count rate decreased to approximately one-tenth of its original value, with a count rate of roughly 3.50 cpm for the blank sample. Subsequently, the detection efficiency was optimized by determining the sample shape and detector size, resulting in an estimated value of 51.2 ± 2.7 %. The theoretically calculated MDA was 0.77 mBq/kg for a 1-h measurement and 0.31 mBq/kg for a 6-h measurement, demonstrating the system's applicability for marine radioactivity analysis.